Options for screening for gestational diabetes mellitus during the SARS‐CoV‐2 pandemic. (10th August 2020) - Simmons, David; Rudland, Victoria L.; Wong, Vincent; Flack, Jeff; Mackie, Adam; Ross, Glynis P.; Coat, Suzette; Dalal, Raiyomand; Hague, Bill M.; Cheung, Ngai Wah
Abstract : The balance between avoiding severe acute respiratory syndrome coronavirus‐2 contagion and reducing wider clinical risk is unclear for gestational diabetes mellitus (GDM) testing. Recent recommendations promote diagnostic approaches that limit collection but increase undiagnosed GDM, which potentially increases adverse pregnancy outcome risks. The most sensitive approach to detecting GDM at 24–28 weeks beyond the two‐hour oral glucose tolerance test (OGTT) is a one‐hour OGTT (88% sensitivity). Less sensitive approaches use fasting glucose alone (≥5.1 mmol/L: misses 44–54% GDM) or asking 20% of women for a second visit (fasting glucose 4.7–5.0 mmol/L (62–72% sensitive)). Choices should emphasise local and patient decision‐making.